2010
DOI: 10.1111/j.1872-034x.2010.00665.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a late evening snack using branched‐chain amino acid‐enriched nutrients in patients undergoing hepatic arterial infusion chemotherapy for advanced hepatocellular carcinoma

Abstract: LES using BCAA-enriched nutrients appears to improve energy metabolism and glucose tolerance in cirrhotic patients with advanced HCC undergoing HAIC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 42 publications
0
35
0
1
Order By: Relevance
“…In addition, whether BCAA supplementation improves energy metabolism was not determined. Harima et al [17] reported that an LES containing BCAA improves energy metabolism and glucose tolerance in LC patients with aHCC undergoing HAIC. However, they did not discuss whether BCAA had an influence on the prognosis of their patients and did not investigate any patients in C-P class B.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In addition, whether BCAA supplementation improves energy metabolism was not determined. Harima et al [17] reported that an LES containing BCAA improves energy metabolism and glucose tolerance in LC patients with aHCC undergoing HAIC. However, they did not discuss whether BCAA had an influence on the prognosis of their patients and did not investigate any patients in C-P class B.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, Hayashi et al [16] reported that BCAA supplementation was associated with a lower incidence of HCC in cirrhosis patients and appeared to prevent liver-related events in C-P class A patients. Furthermore, Harima et al [17] reported that a BCAA-enriched late evening snack improves energy metabolism and glucose tolerance in cirrhosis patients with advanced HCC undergoing HAIC. Therefore, we investigated the effect of BCAA on liver function and the prognosis of LC patients (C-P classes A and B) with aHCC undergoing HAIC in the present retrospective cohort study.…”
Section: Introductionmentioning
confidence: 98%
“…In addition, patients with HCC may suffer from a tumor-induced increase in protein catabolism, which may further aggravate their nutritional status [29,31,32]. A recent study demonstrated that patients with advanced HCC remained in a condition of severe energy malnutrition even when their liver capacity was good [33]. PEM can impair liver regeneration [34], and the strong deterioration of PEM induced by TACE can inhibit the recovery of liver function after TACE.…”
Section: Discussionmentioning
confidence: 99%
“…As these latter reports are about cohort studies, a randomized control trial will be needed. We have reported that a late evening snack using branched-chain amino acid nutrients improved the energy metabolism in advanced HCC patients undergoing hepatic arterial infusion chemotherapy compared with ordinary food [34]. As there are no studies about late evening snacks using branched-chain amino acid nutrients in sorafenib-treated patients with advanced HCC, further investigations are necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Energy metabolism can be analyzed by indirect calorimetry; the non-protein respiratory quotient and oxidation volumes of carbohydrate, fat, and protein are calculated. It has been reported that the non-protein respiratory quotient significantly decreases with the progression of disease severity of LC [33] or with progression of HCC [34]; as a result, the oxidation rate of carbohydrates decreases and that of fat significantly increases. Therefore, advanced HCC patients may require a certain amount of not only skeletal muscle, but also visceral fat, as an energy substrate.…”
Section: Discussionmentioning
confidence: 99%